2020
DOI: 10.1111/chso.12418
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of children’s participation in child protection decision‐making: Tokenistic presence or not?

Abstract: This article examines children's views on and experiences with participation in the child protection system's decisionmaking process. The systematic review follows the PRISMA statement and includes 12 peer-reviewed articles published in academic journals from 2006 to 2017. Findings suggest that children's contact with their worker was limited or nonexistent, which minimised opportunities to express views regarding their situation; child-worker contacts lacked dialogue, information about the process of interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 80 publications
0
48
0
Order By: Relevance
“…Similarly, Jones et al ( 2020 ) suggested that the pandemic would enable the reshaping of CPS to include children as part of the solution. Although listening to children's experiences enables stakeholders to better understand and respond to their needs and support their well‐being, international CPS practices lack children's voices or take a tokenistic approach to listen to children's views (Kosher & Ben‐Arieh, 2020 ; Toros, 2021 ; Falch‐Eriksen et al, 2021 ; van Bijleveld et al, 2020 ). In general, children's participation is believed to benefit both children and society (Björnsdóttir & Einarsdóttir, 2017 ), including in times of crisis.…”
Section: Discussion and Concluding Thoughtsmentioning
confidence: 99%
“…Similarly, Jones et al ( 2020 ) suggested that the pandemic would enable the reshaping of CPS to include children as part of the solution. Although listening to children's experiences enables stakeholders to better understand and respond to their needs and support their well‐being, international CPS practices lack children's voices or take a tokenistic approach to listen to children's views (Kosher & Ben‐Arieh, 2020 ; Toros, 2021 ; Falch‐Eriksen et al, 2021 ; van Bijleveld et al, 2020 ). In general, children's participation is believed to benefit both children and society (Björnsdóttir & Einarsdóttir, 2017 ), including in times of crisis.…”
Section: Discussion and Concluding Thoughtsmentioning
confidence: 99%
“…In addition, the continuity of the relationship between adolescents and educators is an important element, as many adolescents have no experience of stability and continuity due to numerous interventions in which they were involved, as well as the fluctuations of caretakers. Previous studies also confirm the conclusion that adults (professionals) are one of the key elements for the inclusion of children in decision-making, but also for the development of young people's participation capacities [5,14,18,[21][22][23]53].…”
Section: Discussionmentioning
confidence: 58%
“…When expressing their desire to participate, young people mention very specific topics/decisions in which they would like to be involved and which are very important for their quality of life in the institution: the choice of beneficiaries who come into their group, persons with whom they wish to share their living space, the choice of activities in which they want to be involved, and the possibility of influencing the decisions at the level of the social welfare system (such as the amount they get as pocket money). So far, studies have also shown that children in residential care mostly have abundant experience regarding non-participation in everyday decisions, care planning, management meetings related to their life in care, information about admission, the course of treatment, and leaving the social welfare system [14,22,23]. It is important to bear in mind that this group of adolescents exhibit (at least) two vulnerabilities in parallel, i.e., they are both children and beneficiaries of the social welfare system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations